Case-control investigation of occupational exposure to chlorinated solvents and non-Hodgkin's lymphoma. Issue 6 (27th March 2018) - Callahan, Catherine L; Stewart, Patricia A; Friesen, Melissa C; Locke, Sarah; De Roos, Anneclaire J; Cerhan, James R; Severson, Richard K; Rothman, Nathaniel; Purdue, Mark P
Abstract : Objectives: Although many studies have investigated the association between trichloroethylene (TCE) exposure and non-Hodgkin's lymphoma (NHL), less is known about other chlorinated solvents. We extended our previous analysis of occupational TCE exposure in a multicentre population-based case-control study of NHL to investigate associations with five additional chlorinated solvents: 1, 1, 1, -trichloroethane, carbon tetrachloride, chloroform, methylene chloride and perchloroethylene. Methods: Cases (n=1189) and controls (n=982) provided detailed information on their occupational histories and workplace exposure to chlorinated solvents for selected occupations using job-specific interview modules. An industrial hygienist used this information and a review of the literature to assess occupational exposure to chlorinated solvents. We computed ORs and 95% CIs for different exposure metrics, with the unexposed group as the referent. We also computed ORs by NHL subtype. Results: High cumulative hours exposed to carbon tetrachloride was associated with NHL (>520 hours: OR 1.9; 95% CI 1.0 to 3.6; Ptrend =0.04). This association remained after restricting to jobs with high-intensity exposure (OR 2.0; 95% CI 1.1 to 3.8; P=0.03) and ≥90% exposure probability (OR 2.1; 95% CI 1.0 to 4.3; P=0.03), adjusting for TCE (OR 2.1; 95% CI 1.0– to 4.1; P=0.04) and incorporating a 15-year lag (OR 1.9; 95% CI 1.0 to 3.6; P=0.06). The other evaluated chlorinated solvents were not associated with NHL. Conclusions: This is the first study using high-quality quantitative exposure assessment methods to identify a statistically significant elevated association between occupational exposure to carbon tetrachloride and NHL. Our findings, although limited by a small number of exposed cases, offer evidence that carbon tetrachloride may be a lymphomagen.